2019
DOI: 10.3168/jds.2019-16590
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dairy on-farm high-temperature, short-time pasteurization of milk on the viability of Mycobacterium avium ssp. paratuberculosis

Abstract: Feeding pasteurized milk to suckling calves is a popular practice used increasingly on dairy farms. Waste milk is frequently fed to calves because of its high nutritional value and economic benefits compared to milk replacement products. However, one of the disadvantages of feeding waste milk is the potential for exposure to a high number of bacterial contaminants, which may lead to serious illnesses or infections in calves. One of these contaminants is Mycobacterium avium ssp. paratuberculosis (MAP), the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…MAP research coupled with waste milk feeding in animals had 30% growth between 2017–2019. This is due to the possibility of MAP transmission due to feeding of waste milk to calves [ 71 , 72 ]. Leao et al [ 71 ] found that 89.2% of farms enrolled in their study fed waste milk to calves, without pasteurisation except one farm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAP research coupled with waste milk feeding in animals had 30% growth between 2017–2019. This is due to the possibility of MAP transmission due to feeding of waste milk to calves [ 71 , 72 ]. Leao et al [ 71 ] found that 89.2% of farms enrolled in their study fed waste milk to calves, without pasteurisation except one farm.…”
Section: Resultsmentioning
confidence: 99%
“…Other factors involved in MAP positivity from feeding waste milk to calves include animal origins (the incidence of MAP in farm with herds from a single origin was 3.5 times higher and 1.9 times higher in farms with herds from multiple origins), and calving area (multiple cow calving increase the risk of MAP positivity by 1.5 compared with single pens) [ 71 ]. Generally, waste milk pasteurisation has been found inadequate to limit MAP transmissions to calves as viable cells (≥1000 MAP cells/mL) were still present after a short pasteurisation period [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, other diseases have been associated with MAP, such as sarcoidosis, Blau syndrome, type 1 diabetes, Hashimoto's thyroiditis, and multiple sclerosis (9,(11)(12)(13)(14)(15)(16). Regarding the transmission sources, MAP may contaminate food for human consumption, such as dairy and meat products, infant formula (17)(18)(19), and water (6,20); and MAP seems to resist pasteurization treatment of milk at 72 • C for 15 s [high-temperature, short-time (HTST) pasteurization] (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Viable MAP were found in pasteurized milk, cheese, and even in dried milk products such as infant formula [ 12 , 13 , 14 ]. This might have been caused by post-processing contamination, but there is also evidence of MAP being able to survive the pasteurization process [ 15 , 16 , 17 , 18 , 19 ]. The mechanisms behind this tenacity, however, are not fully understood and have been vigorously discussed over the last years [ 8 , 20 ].…”
Section: Introductionmentioning
confidence: 99%